Hereditary Afibrinogenemia: Rare Bleeding Disorder Presenting with Spontaneous Extradural Hematoma – A Brief Review - Guru Dutta Satyarthee; Ashok K. Mahapatra (Indian Journal of Neurosurgery)
Abstract Afibrinogenemia is considered as rare hereditary bleeding disorder with autosomal recessive genetic transmission, caused by mutations of any one out of the three genes located on chromosome 4, responsible for coding of three polypeptide chains, constituents of fibrinogen. Clinical manifestation include spontaneous bleeding, bleeding following trivial trauma, and excessive profuse bleeding during major trauma constitute commoner manifestations. Replacement therapy remains main treatment of bleeding episodes using plasma-derived fibrinogen concentrate. However, fresh frozen plasma and cryoprecipitate, recombinant fibrinogens are considered as alternative treatment options. The authors reports a 2-year-old girl, diagnosed as case of hypofibrinogenemia since birth and was under regular supervision of pediatric hematologist, getting fresh frozen plasma replacement therapy every third weeks, developed extradural hematoma and was managed surgically with good outcome.